2023
DOI: 10.1049/sfw2.12091
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Scientific programming using optimized machine learning techniques for software fault prediction to improve software quality

Abstract: The amount of time and money required to finish a software project and distribute the final product increases when there are bugs in the programme. Software procedures like defect monitoring and repair may be both costly and time-consuming to complete. Because it is difficult to locate and correct every defect in a product, it is essential that the negative effect of those defects be minimised in order to provide a result that is of better overall quality. The process of identifying troublesome sections of sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In this paper, other classifiers are used to show the effectiveness of our proposed method. These classifiers are the K‐Nearest neighbor (KNN) [50], the probabilistic neural network (PNN) [51], and the Naïve Bayes (NB) [52] and the acquired results are shown in Tables 16 and 17. As can be seen from Table 16, our proposed method has better results than other classifiers.…”
Section: Results Of the Identification Of The Harmonic Sourcementioning
confidence: 99%
“…In this paper, other classifiers are used to show the effectiveness of our proposed method. These classifiers are the K‐Nearest neighbor (KNN) [50], the probabilistic neural network (PNN) [51], and the Naïve Bayes (NB) [52] and the acquired results are shown in Tables 16 and 17. As can be seen from Table 16, our proposed method has better results than other classifiers.…”
Section: Results Of the Identification Of The Harmonic Sourcementioning
confidence: 99%
“…Table 1 encapsulates a summary of previous research endeavors pertaining to SDP applied in open-source projects. [5] introduced the ACO-SVM model, which amalgamates the Ant Colony Optimization (ACO) technique with the Support Vector Machine (SVM) model. ACO serves as an optimization technique for feature selection.…”
Section: Software Defect Prediction Applied In Open-source Projectsmentioning
confidence: 99%
“…Quality management and testing expenditures aimed at guaranteeing reliability constitute a substantial portion of overall software development costs. The expense is escalating exponentially to rectify software defects in the later stages of development [5]. Hence, utilizing available resources and minimize defects at the initial phase of a software development are crucial to obtaining high-quality outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to validate the efficacy of their proposed algorithm, they compared it against eight distinct public data sets, in which the results showed that their suggested work handles the multi-objective undersampling SDD problem more effectively. Shafiq et al [28] developed an approach for SDD using ML to enhance software quality. They used PC1 data set as input data.…”
Section: Literature Reviewmentioning
confidence: 99%